Treatment Response Monitoring Using a Tumor-Informed Circulating Tumor DNA Test in an Advanced Triple-Negative Breast Cancer Patient: A Case Report - Georges Azzi; Shifra Krinshpun; Antony Tin; Minu Maninder; Allyson Koyen Malashevich; Meenakshi Malhotra; Ruben Ruiz Vega; Paul R. Billings; Angel Rodriguez; Alexey Aleshin (Case Reports in Oncology, 2022)
Triple-negative breast cancer (TNBC) is highly aggressive disease that is often refractory to surgery and multiple lines of therapy. Although the repertoire of FDA-approved treatments has expanded, there is an unmet need for biomarkers that can aid in appropriate selection and timing of therapy. We present a case of highly aggressive treatment-resistant TNBC that employed a comprehensive genomic profiling (CGP)-based assay to identify therapeutic targets, followed by longitudinal circulating tumor DNA (ctDNA) testing. For this, a tumor-naïve next-generation sequencing-based targeted panel was used to aid in therapy selection, along with longitudinal personalized and tumor-informed ctDNA testing to monitor tumor response to treatment. Longitudinal ctDNA testing using the tumor-informed assay detected post-surgical molecular residual disease, and rise in ctDNA levels during the surveillance period provided rationale for switching between four lines of therapy. Overall, the combined use of CGP assay with longitudinal ctDNA testing resulted in a potential prolonged survival in this highly aggressive case of TNBC.